A 28‐GHz reconfigurable 1‐bit substrate‐integrated‐waveguide based phase shifter. Issue 15 (2nd December 2021) - Acri, G.; Podevin, F.; Ferrari, P.; Pistono, E.; Boccia, L.
Abstract: A switched‐line substrate integrated waveguide 1‐bit phase shifter is designed and measured at 28 GHz. Reconfigurability is achieved through a set of floating metallized vias whose connection to the waveguide top and bottom layers can be controlled using PIN diodes. The reconfigurable vias are used to dynamically create alternative paths having different phase delays. A three‐metal layer printed circuit board stack‐up is employed to fully integrate the diode biasing network and to ease the routing of the bias signal. The high integration of the proposed configuration makes it well suited for the implementation of reconfigurable Butler matrices. The phase shift offset between the two states of this digital 1‐bit phase shifter equals 262° at 28 GHz, leading to a measured figure of merit of 161°/dB, and input 1‐dB compression point over 20 dBm. The total area is 13.72 × 10.9 mm without feeding lines and bias.